Addition to the fauna of aphids (Homoptera, Aphididae) Katon-Karagay national park (Kazakhstan Altai) (Experimental biology, 2015)
In Katon-Karagay National nature park has identified 28 species. Now from the territory of park is known of 239 aphidspecies belonging to 82 genera of the families Adelgidae (6 species, 2.5% of the fauna), Aphididae (233, 97.5%). To the list of genera added Monaphis, Capitophorus, Xerobion, Cryptomyzus. Genera: Pemphigus (5 species), Cinara (12),Sipha (4), Chaitophorus (11), Pterocomma (4), Aphis (54), Brachycaudus (6), Dysaphis (5), Semiaphis (4), Cavariella (5), Coloradoa (3), Nasonovia (3), Acyrthosiphon (10), Macrosiphum (4), Uroleucon (14), Macrosiphoniella (12) are the most richly represented in the fauna of the national park. 15 species: Cinara mongolica, Monaphis antennata,Chaitophorus tremulae sorini, Xerobion alakuli, Aphis esulae, A. mohelnensis, A. epilobii, Brachycaudus prunicola,Dysaphis affinis, Capitophorus hyppophaes, Aulacorthum cylactis, Macrosiphum atragenae, Macrosiphum euphorbiae,Uroleucon mulgedii, Macrosiphoniella nigropilosa are found in the Kazakhstan Altai for the first time. Cinara mongolica, Monaphis antennata are in Kazakhstan for the first time. Thus, taking into account the new found materials in the Kazakhstan Altai currently identified 380 species of aphids. On the territory of the Katon-Karagay Park currentlyidentified 62.9% of the species that live in the Kazakhstan Altai.
Keywords: aphids; fauna; Kazakhstan Altai